Epidemiološke i kliničke karakteristike Clostridium difficile infekcije prije i tokom COVID-19 pandemije: Epidemiological and clinical characteristics of Clostridium difficile infections - Knežević, Darija; Jović, Duška; Petković, Miroslav (Scripta Medica, 2023)
Background/Aim: Diarrhoea that occurs as a result of the presence of Clostridium difficile (reclassified as Clostridoides difficile) is usually manifested as a hospital infection, usually after antibiotic treatment. The study aim was to assess the incidence, characteristics and outcomes of hospitalised patients with healthcare – associated Clostridioides difficile infection ( HA - CDI) before and during the COVID-19 pandemic. Methods: This retrospective cohort study included patients older than 18, who met the HA - CDI case definition. The CDI diagnosis was made by demonstrating toxins A and B in stool samples using an immunochromatographic assay test and polymerase chain reaction (PCR). Results: The incidence of HA - CDI has significantly decreased from the pre- COVID-19 period to the COVID-19 period (11.04 per 10,000 vs 6.49 per 10,000, p < 0.001). Before establishing the HA - CDI diagnosis, 41.4 % of patients used one antibiotic, 25.9 % used two and 11.2 % were treated with three or more antibiotics. Almost one half of the applied antibiotics were from the group that represents high risk for the development of HA - CDI. Multivariable logistic regression analysis showed that older age (OR = 3.4; 95 % CI = 0.9-12.4; p = 0.038) and complicated disease course (OR = 11.8; 95 % CI = 2.6-53.6; p ≤ 0.001) were associated with a higher risk of death. Conclusion: The incidence of HA - CDI has decreased during the observed period of the COVID-19 pandemic, however, no clear connection between the impact of the pandemic and incidence reduction was found. Due to unfavourable outcome of the treatment of HA - CDI patients during COVID-19 pandemic, the rational use of antibiotics is necessary.